POLICY HARMONISATION IN LAND GOVERNANCE THROUGH SPATIAL DATA INTEGRATION AND INSTITUTIONAL COORDINATION - Chairul Annam; Billy Balovan Langi; Ridho Rachmawan (Adisam Publisher, 2025)
This study aims to analyze how the integration of spatial data and inter-agency coordination contribute to policy harmonization in land governance. Using a descriptive, qualitative approach, this study examines the experiences and perspectives of land officials, spatial planners, geospatial data managers, and stakeholders at both central and regional levels. The study's results indicate that regulatory fragmentation and overlapping authority between institutions continue to be the primary obstacles to achieving a consistent land policy. Spatial data integration through Spatial Data Infrastructure (SDI) has been proven to enhance information consistency, minimize data duplication, and enhance cross-sector decision-making processes. However, the effectiveness of data integration is greatly influenced by the quality of institutional coordination, including data sharing mechanisms, technical standards, and alignment of mandates between agencies. The study also found a capacity gap between the central and regional governments, with implications for uneven policy implementation. These findings confirm that policy harmonization requires synergy between geospatial technical innovation and institutional reforms that encourage cross-sectoral collaboration. Thus, research makes a significant contribution to the development of a more integrated, transparent, and responsive land governance model that addresses development challenges.